Combating Workplaces Corruption - Ismail, Fadillah; Nesreen Ibrahim Owaida, (Advances in Humanities and Contemporary Studies, 2023)
The study emphasises the necessity to address workplace corruption in Malaysia. It discusses the causes, effects and how to address the corruption issues happened in workplace Malaysia. Individual factor, economy development, organizational culture and religious, political leadership power has led to the causes of corruption in workplace. In addition, effects like income distribution, consumption pattern, government budget, economic reforms are highlighted in the paper. The paper also touched upon the remedial measure like leadership, credibility, involving people, responsible press, oversight bodies and improving institution as remedial measure to address the issue.